Comparison of Growth and Production Performance between Male and Female Giant Freshwater Prawn in Combination with Mola - Fatema, K; Wahab, MA; Pervin, R; Khan, MSR; Roy, HC (Journal of Environmental Science and Natural Resources, 2012)
An experiment was conducted to compare growth and production performance between all-male and all-female giant freshwater prawn (Macrobrachium rosenbergii) in combination with mola (Amblypharyngodon mola) at the Fisheries Field Laboratory, Bangladesh Agricultural University, Mymensingh, Bangladesh. The research was carried out for a period of 120 days in nine earthen ponds with an average depth of 1.2 m. The experiment had three treatments, viz. polyculture of all-male prawn with mola (stocking density 20,000 ha-1), monoculture of all-male prawn and monoculture of all-female prawn were treated as T1, T2, and T3, respectively with three replications of each and prawn stocking density was 30,000 ha-1 in all the treatments. Formulated sinking feeds were applied twice daily for prawn, and assuming 80% survival feeding rates were gradually reduced to 10-5% of body weight from the beginning to the last month. All water quality parameters (except transparency, chlorophyll-a and plankton) did not vary statistically significantly (P>0.05) among the treatments. Survival of prawn in respective of gender was lower in monoculture than in polyculture with mola, but did not vary significantly (P>0.05). Considering growth and production performance in all treatments, the male prawn showed better growth and production performance than female prawn and the highest gross and net production was recorded in treatment T1, therefore, polyculture of all-male prawn with mola is better than monoculture. DOI: http://dx.doi.org/10.3329/jesnr.v4i2.10163 J. Environ. Sci. & Natural Resources, 4(2): 137-142, 2011